The Minister of Research, Technology, Education, and Culture Issued a Crisis Communication in Response to the Pros and Cons of Ministerial Regulation No. 30 of 2021 on the Prevention and Handling of Sexual Violence in Higher Education - Taffani Rahma Yuandara (Budapest International Research and Critics University, 2022)
This research aims to prevent the occurrence of sexual violence in higher education, which is increasingly happening in various parts of Indonesia. The research method uses library research. The primary data source uses regulation Number 30 of 2021 concerning the prevention and handling of sexual violence in universities. The primary data source is regulation Number 30 of 2021, and the secondary data source uses relevant research literature. At the same time, the data analysis uses documentation analysis. The results of this study state that with regulation Number 30 of 2021 concerning the prevention and handling of sexual violence in universities, it is hoped that the problems faced by large organizations, including universities in Indonesia, can be resolved in stages. In addition, relationships with other organizations and civitas can be formed in such a way that the settlement.